Tanèyan Lanjhâng as an Indigenous Parenting System for Supporting Early Childhood Social Skill Development: A Qualitative Study - Latif, Muhammad Abdul; Nadlifah, Nadlifah; Alahmari, Sarah A (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Indigenous parenting systems remain underexplored in early childhood social development research, particularly within non-Western cultural contexts. Addressing this gap, this study examines how Tanèyan Lanjhâng, a traditional Madurese communal living system, functions as an indigenous parenting framework that supports social skill development in early childhood. Using a qualitative descriptive design, data were collected through semi-structured interviews with four early childhood teachers selected via purposive sampling from two early childhood education institutions in Bangkalan Regency, Indonesia. The data were analyzed thematically following Braun and Clarke’s six-phase approach. The findings are organized into four interrelated themes: communal interaction, which provides children with continuous opportunities to practice communication, cooperation, and emotional regulation; solidarity and mutual assistance, fostering prosocial behaviors such as helping, sharing, and group participation; politeness as moral socialization, strengthening children’s understanding of social norms and respectful behavior; and social adaptability, enabling children to adjust effectively to diverse social environments. Together, these themes demonstrate that Tanèyan Lanjhâng embeds social learning naturally within daily family life. This study contributes academically by extending culturally grounded perspectives in early childhood education and highlighting indigenous knowledge as a valuable resource for social development frameworks. Globally, the findings offer insights for multicultural and context-responsive early childhood practices beyond Western-centric models. However, the study is limited by its small sample size and localized context, suggesting the need for further research involving diverse communities and mixed-method approaches.